Telaah Etika Bisnis Islam Terhadap Perilaku Pelaku Afiliasi Dalam Promosi Di Media Sosial: Studi Pada Pelaku Afiliasi Platform Tiktok - Nuraini; Abdul Mutalib, Ahmad (MBISKU: Jurnal Manajemen Bisnis dan Keuangan, 2025)
This study discusses Islamic business ethics towards the behavior of affiliate actors in promotion on TikTok. The purpose of this study is to determine how the behavior of affiliate actors in promotion on TikTok and how Islamic business ethics towards the behavior of affiliate actors in promotion. This study includes field research with a qualitative approach, the data collection techniques used are interviews and documentation. The subjects of this study include 3 affiliates, namely A. Siti Patimah, Syakila Safitri, and Sulviana, the object of this study is Islamic business ethics in the promotional activities of affiliate actors on TikTok. The data analysis techniques in this study include data reduction, data presentation, and drawing conclusions. The results of the study show that (1) In conducting promotions, the three affiliates prioritize the authenticity of the content used, as well as in product selection, they tend to be selective and have certain considerations to ensure that the promoted product does not harm the audience, while in delivering information, they prioritize clarity & appropriateness of information, they also apply special strategies to support the progress of their affiliates. (2) The behavior of the three affiliates shows compliance with the principles of Islamic business ethics. In this case, siddiq is shown by the use of original promotional content, amanah is shown by responsibility in product selection, tabligh is shown by the delivery of clear and appropriate information, and fathonah is shown by the application of smart promotional strategies.